Aprēķins: rm68p7 - 1

 s^2  = 
 
 ( (x1-x_v)^2* m1+ (x2-x_v)^2* m2+ (x3-x_v)^2* m3)
/ (n-1)
 s^2 =  
 ( (x1-x_v)^2* m1+ (x2-x_v)^2* m2+ (x3-x_v)^2* m3)
/ (n-1)
 = 
 s^2 =  
 x1^2* m1
/ (n-1)
- 
 2* x1* x_v* m1
/ (n-1)
+ 
 x_v^2* m1
/ (n-1)
+ 
 x2^2* m2
/ (n-1)
- 
 2* x2* x_v* m2
/ (n-1)
+ 
 x_v^2* m2
/ (n-1)
+ 
 x3^2* m3
/ (n-1)
- 
 2* x3* x_v* m3
/ (n-1)
+ 
 x_v^2* m3
/ (n-1)
 = 
s = saknis( 
 x1^2* m1
/ (n-1)
- 
 2* x1* x_v* m1
/ (n-1)
+ 
 x_v^2* m1
/ (n-1)
+ 
 x2^2* m2
/ (n-1)
- 
 2* x2* x_v* m2
/ (n-1)
+ 
 x_v^2* m2
/ (n-1)
+ 
 x3^2* m3
/ (n-1)
- 
 2* x3* x_v* m3
/ (n-1)
+ 
 x_v^2* m3
/ (n-1)
)
 = 
s = saknis( 
 m1* x1^2
/ (n-1)
- 
 2* m1* x1* x_v
/ (n-1)
+ 
 m1* x_v^2
/ (n-1)
+ 
 m2* x2^2
/ (n-1)
- 
 2* m2* x2* x_v
/ (n-1)
+ 
 m2* x_v^2
/ (n-1)
+ 
 m3* x3^2
/ (n-1)
- 
 2* m3* x3* x_v
/ (n-1)
+ 
 m3* x_v^2
/ (n-1)
)
 =